Differential Constitutive Relation for Creep of Large-Stone Porous Asphalt Mixture - Yang, Bin; Mo, Sihao; Wang, Longhui; Ji, Ye (Asian Journal of Chemistry, 2014)
As a typical type of non-linear viscoelastic-plastic material, the large-stone porous asphalt mixture (LSPM) has very complex physical behaviour. Via connecting a Burgers model to viscoplastic material body in series, the viscoelastic-plastic constitutive equation was obtained. The viscoelastic-plastic constitutive model was then combined with the law of creep damage, which was used to describe the damage variation of the LSPM, to build the viscoelastic-plastic damage constitutive model. This resulting model can simulate the creep deformation behaviour of the LSPM relatively well. Moreover, the uniaxial compression creep tests on the LSPM were conducted in the MTS testing machine, through which the parameters for the viscoelastic-plastic damage constitutive model were determined. Finally, the approximate functions describing the relationships of the parameters versus temperature and stress were constructed.